Analisis Manajemen Risiko pada UMKM di Kabupaten Bandung Studi Kasus: AMEL COLLECTION - Reihan Ahmad Nurhakim; Dhafin Al-Rasyid Dhafin Al-Rasyid; Elky Rimba Priatna; Aris Kurniawan; Alfiana Alfiana (Indonesia Economic Journal, 2026)
This study looks at how small and medium businesses handle risks, using the example of AMEL COLLECTION in Bandung Regency. The research uses a descriptive qualitative method to find the main risks that could stop the business from running smoothly. These risks include problems with the market, marketing, operations, finances, and the workforce. Most of these risks are considered high, and they come from things like changes in customer demand during certain seasons, not having enough different products, poor use of digital marketing, not keeping good financial records, and not having enough workers. Using a risk matrix, the study shows that these issues need to be addressed right away. Suggestions to fix these problems include better online promotion, better control of inventory and sales, more organized financial reports, and hiring more trained employees. Managing risks well is important for making the business more stable and helping it grow in a sustainable way.